3D h9e peptide hydrogel: An advanced three-dimensional cell culture system for anticancer prescreening of chemopreventive phenolic agents. (December 2019) - Xu, Jingwen; Qi, Guangyan; Sui, Chunxia; Wang, Weiqun; Sun, Xiuzhi
Abstract: Traditional 2D monolayer cell culture model may overestimate chemopreventive agent's response due to lacking physiological relevance in three-dimensional microenvironment. This study was aimed to apply a novel 3D h9e peptide hydrogel cell culture system to evaluate the anticancer efficacy of chemopreventive phenolic acid on hepatocarcinoma HepG2 and colon adenocarcinoma SW480 cells. Both cell lines grew better in this 3D system with better cell growth and longer exponential phase than that in 2D model. Chlorogenic acid (CGA), known as a chemopreventive phenolic acid, at 0–40 μM for 72 h inhibited cell growth but not viability in both HepG2 and SW480 cells. The inhibition was much less potent in 3D system with an IC50 value of 58.0 ± 15.8 or 285.6 ± 75.4 μM when compared with 2D model with IC50 of 5.3 ± 0.3 or 12.0 ± 2.5 μM for HepG2 or SW480, respectively. Furthermore, the recovery of cells grown in 3D system after post-CGA appeared faster than 2D model. Taken together, an advanced 3D model has been established with favoring cell growth and less susceptible to inhibitory treatments in contrast to 2D model, thus predict closely to in vivo situation and may bridge the gap of in vitro to in vivo for prescreening chemopreventive agents for cancer prevention. Graphical abstract: Unlabelled Image Highlights: 3D h9e peptide hydrogel cell culture favored HepG2 and SW480 cell growth. HepG2 and SW480 cells in 3D culture were more resistant to chlorogenic acid. 3D culture may bridge the gap between in vitro 2D culture and in vivo animal model.